Professor A. A. Sokolsky – A Russian Emigrant from Lithuania Who Rewrote the History of Saint-Petersburg in Florida - Марцинкявичюс, Андрюс (Literatūra, 2022)
The article explores biography and various aspects of public activity of the Russian refugee from Lithuania, lawyer, professor of Russian language and literature at the University of South Florida Anatole Sokolsky (1993–2006). Memoirs and articles published by him in the USA were used as the basic empirical material and the documents from the Lithuanian Central State Archive and private collection of the Sokolsky family served as auxiliary sources for the research. There is a lack of studies that analyze the history of representatives of Russian intelligentsia who were forced to escape Lithuania in the period of World War II (from 1939 to 1945) because of the danger of the Soviet regime. Publications by Sokolsky do not represent an example of professional literature, but it allows us to find out more not only about personal destiny and worldview of the author, the results of his social activities in favor of the Russian diaspora, but also about the life of Russian intelligentsia in the periods of interwar, World War II and emigration to the West.